Preservation, production, and packaging optimization in SMEs: A study on 'Keripik Lumba-Lumba' - Ismianti, Ismianti; Rahman, Ibnu Fahrul; Lasmana, Amorette Garnetta; Anisah, Eka Nur (OPSI, 2024)
'Keripik Lumba-Lumba' is a Small and Medium-sized Enterprise (SME) that specializes in the production of cassava chips and banana chips. This SME faces several problems such as raw material shrinkage due to shipping, double work, and different product shelf life between each distributor. This research designed a solution to the problems in the SME with shelf-life preservation, job design, and new packaging design. A truck equipped with a temperature control system was designed to prevent the banana raw materials from rotting during transport. Wooden boxes were also provided in the truck for separating containers, these wooden boxes were lined with a solid mixture of KMnO4, clay, and ash. To solve the problem of the production process within ‘Keripik Lumba-Lumba’, the job design system can be changed to schedule and allocate employees according to their respective tasks. On the issue of shelf life difference between convenience stores and distributors, the packaging material for distributors can be changed from plastic to aluminium foil. This will allow ‘Keripik Lumba-Lumba’ to continue to grow with the application of technology in the process of delivery, storage, packaging as well as changes in the work system.